Developing contrastive pragmatics interlanguage and cross-cultural perspectives - Pütz, Martin; Neff-van Aertselaer, JoAnne (Studies on language acquisition, 2008)
The present volume is a collection of papers on Contrastive Pragmatics, involving research on interlanguage and cross-cultural perspectives with a focus on second language acquisition contexts. The subdiscipline of pragmatics is seen from a multilingual and multicultural perspective thus contributing to an emerging field of study, i.e. intercultural pragmatics which can be made fruitful to second language teaching/learning and contrastive analysis. The book is an important contribution to general linguistics, pragmatics, cross-cultural communication, second language acquisition, as well as min
Keywords: Pragmatics; Intercultural communication; Interlanguage (Language learning); Second language acquisition; minority languages; multilingualism; second language acquisition